Petunia in Lapindo Mud Area as Verticultural Land - Suci Putri Fetindah; Ardin Wira Yuda; Mahendra (Universitas Muhammadiyah Sidoarjo, 2022)
The area affected by the Lapindo mud is contaminated with heavy metals, one of which is lead (Pb) which is above the threshold of 3.0 mg/kg. The treatment is to apply a strategy through phytoremediation to minimize excess heavy metal content. One of the plants that is effectively used for phytoremediation is Petunia because it is resistant to heavy metals. This study aims to develop the potential of land affected by the Lapindo mud by using vertical planting methods, utilizing the capillarity of water in the absorption of plant nutrients to decorate the affected land and assisting the absorption of lead type heavy metal (Pb) in maximizing the effectiveness of related uses. The research is described through a vertical design around the Lapindo mud area. The method used to apply the technology is the practice of planting on vertical media and supervision in the form of fertilization and plant maintenance until the harvest period. The research data were analyzed using quantitative descriptive statistics. The results of the evaluation based on the indicators of the success of the activity showed that more than 90% of local residents and tourists were interested in the management of the land phytoremediation program using the Petunia ornamental plant verticulture method and the plant was able to absorb excess heavy metals (Pb).